Polymorphisms and haplotypes in VDR gene are associated with female idiopathic infertility. (2nd April 2020) - Djurovic, Jelena; Stamenkovic, Gorana; Todorovic, Jelena; Aleksic, Natasa; Stojkovic, Oliver
Abstract: Unexplained infertility refers to the absence of a definable cause of reproductive failure. Vitamin D receptor (VDR) acts as a transcription factor and regulates a number of vitamin D-responsive genes, including those involved in the immune system. Recent finding that VDR is expressed in reproductive tissues suggests a possible importance of vitamin D in pregnancy. We conducted a case-control study to examine the association of polymorphisms in VDR gene with reproductive success. DNA from 117 female patients with unexplained infertility and 130 fertile controls was isolated from peripheral blood and VDR genotypes (FokI, BsmI, ApaI and TaqI) were detected by PCR-RFLP. Haplotypes were determined using Haploview software. Our results show significant association of FokI and BsmI polymorphisms with infertility ( p  < 0.05). The haplotype analysis confirmed strong linkage disequilibrium between closely positioned BsmI, ApaI and TaqI polymorphisms. Two haplotypes were associated with infertility: (i) haplotype bAT was increasing the risk for secondary infertility; while (ii) haplotype BAT had a protective role against primary infertility ( p  < 0.05). By changing the expression and the activity of VDR gene, which leads to the change in expression of vitamin D-responsive genes, these polymorphisms and haplotypes could possibly have an effect on immune system in the female reproductive tract.